Evaluasi dan Rekomendasi Program Pencegahan Kekerasan Seksual di Lingkungan Sekolah: A Systematic Literature Review - Bertha Kristiyanti; Nisa Simon, Ainun; Afiyata Vika, Dinda; Tinduku, Beatrix (Universitas Paramadina, 2024)
Sexual violence has become a global issue that is of serious concern in various countries. In the school context, harmful sexual behavior has become a global problem since the 1990s and a major challenge for society. High rates of child abuse and sexual violence have highlighted the need for focused interventions to educate young students about sexual risks and protection against harmful behavior and to raise awareness of their rights to be protected. This research aims to find out the results of the evaluation of preventive programs regarding sexual violence that are already running in Indonesia and provide recommendations regarding other preventive programs that can be implemented in Indonesia. This research uses the systematic literature review (SLR) method. Article searches were carried out through the Scopus, ScienceDirect, and Garuda databases involving 15 relevant articles regarding preventive interventions for sexual violence. All articles reviewed were also assessed for suitability according to the Mixed Method Appraisal Tool (MMAT) guidelines. Education-based interventions, which include bystander training, psychoeducation, media literacy, and legal education, have been shown to increase awareness and prevention of behavior of sexual violence among students. School and community-based intervention programs are also helpful in preventing sexual violence and creating safer environments.